A organização escolar para a integração das novas tecnologias de informação e comunicação ao processo de ensino e aprendizagem - Castro, Márcia Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to carry out an analysis of the integration of new Information and Communications Technology (ICT) into the municipal schools of elementary education the city of Araraquara, focusing on the collective work of the school staff. It is assumed that the integration of the ICT into the teaching and learning process goes beyond the classroom and the teacher's actions, but it is the responsibility of the whole pedagogical team. The bibliographic review was based on the areas of Information and Communications Technology in Education and School Management. The data collection instruments were: Likert-type scale questionnaire designed from the synthesis of issues studied in both areas and applied to the teachers, with the objective of analyzing the work organization in the school for the integration of ICT to the teaching and learning process; demographic questionnaire, in order to characterize the teachers' profile; and a record form about the Pedagogical Project of the schools, so as to verify how these schools approach the theme of new technology use in the educational process. The results show an increasing tendency among teachers to regard Information and Communications Technology as a fundamental tool for teaching and learning and that its integration into the school universe depends on the whole pedagogical team working together. However, this tendency was not shown in the Pedagogical Project actions planned by the school staff. It is possible to conclude that there is a need for a theoretical and methodological foundation, which can guide the work of teachers and school managers for the use of these technologies. This current need results in the lack of systematic planning for the integration of ICT into school education

O presente trabalho tem como objetivo realizar uma análise da integração das tecnologias de informação e comunicação (TIC) nas escolas municipais de Ensino Fundamental da cidade de Araraquara, com enfoque no trabalho coletivo da equipe escolar. Parte-se do pressuposto de que a integração das TIC ao processo de ensino e aprendizagem vai além da sala de aula e da ação individual do professor, mas é responsabilidade de toda a equipe pedagógica da escola. A revisão bibliográfica se baseou nas áreas de tecnologias de informação e comunicação na educação e gestão escolar. Os instrumentos para a coleta de dados foram: questionário do tipo Escala Likert, aplicado aos professores, elaborado a partir da síntese de assuntos das duas áreas, objetivando analisar a organização do trabalho na escola para a integração das TIC ao processo de ensino e aprendizagem; questionário demográfico-ocupacional, a fim de caracterizar o perfil dos professores; e uma ficha de registro sobre o Projeto Pedagógico das escolas, com o intuito de verificar como estas abordam o tema do uso das novas tecnologias no processo educativo. Os resultados apontam para uma tendência crescente entre os professores em considerar as tecnologias de informação e comunicação ferramentas fundamentais para o ensino e a aprendizagem e que sua integração ao universo escolar depende do trabalho de toda equipe pedagógica. No entanto, essa tendência não se concretizou no Projeto Pedagógico em ações planejadas pela equipe escolar. Conclui-se que há uma carência de fundamentação teórica e metodológica que embasam e direcionem o trabalho de professores e gestores para o uso das tecnologias, resultando na ausência de planejamento sistemático para a integração das TIC na educação escolar
Keywords: Educação; Aprendizagem; Tecnologia da informação; Ensino; Curriculos; Education